Creating an organizational and economic mechanism for energy enterprises - Savchenko, Olga; Ugur, Turan; Veriutina, Viktoriia (Trakia University of Stara Zagora, Bulgaria, 2020)
The subject of the study is to develop an integrated sustainable development mechanism for small and medium enterprises (SMEs) operating or will be operating in the energy sector in Ukraine and to offer these companies an alternative perspective in line with UNDP's goals. The focus of the paper is to provide a more advanced structure for SMEs and create a perspective for them to make the right decisions. Along with all targets, it aims to draw attention to Ukraine's energy security, efficiency problems, and some structural deficiencies and to further develop the energy sector with innovative solutions and examples from Europe. The main purpose of the organizing process is to combine the elements necessary for organizational success effectively and efficiently. While organizing function is carried out effectively, the staff will understand the roles and functions expected from him and understand the purpose of the organization. In this study, the authors developed a perspective on SMEs aiming to develop in the energy sector. As a result of the researches, it is emphasized how important Energy 4.0 is in terms of development, to give examples from the world experience and to show the direction of energy trends in order to point out the problems that draw attention.
Keywords: sustainable development; energy efficiency; energy 4.0; energy security; Ukraine